Chemical and physical restraint of patients - Cunha, Madalena (2018)
Problem Statement: The physical and chemical restraint of patients, despite being often applied with no real scientific basis, has always been part of nursing practice in caring for the ill people. Research Questions: What is the level of knowledge over in nursing about physically and chemically restraining? Purpose of the Study: Evaluate the level of knowledge of nurses on physical and chemical restraint of patients. Research MethodsThe cross-sectional descriptive study was conducted by collecting data using a survey on the knowledge that physically and chemically restraining patients. To this end, a convenience sample was assessed consisting of 156 nurses aged between 24 and 57 (average being 35.11), 79.2% of which were female and 20.8% were male. Findings: The majority (92.3%) consider the physical restraint is a way of ensuring the patient's safety. The level of knowledge reveals that the majority (53.1%) have knowledge on the physical and chemical restraint of patients, noting that 46.9% have a good level of knowledge, 6.2% a reasonable level of knowledge and 46.9% have a weak level of knowledge on the subject. Conclusions: Given the results, there arises the concern to include training on the physical and chemical restraint of patients in the study plan, as well as implementing the training and simulated practice of restraining measures, giving future nurses the transferable skills needed in clinical practice.